Falling angel - Moody, Susan (Coronet, 1998)
Flora never wants children, but when her sister, Georgie, is killed, Flora ends up assuming the role of mother to her sister's baby. When the serial killer is caught, he is adamant that Georgie was not his victim and Flora is determined to find out who really murdered her sister.